Features of labor and postpartum period in women with iron deficiency anemia - A. S. Atajanyan; M. S. Zaynulina; O. L. Molchanov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2019)
Relevance. The relevance of improving the treatment of pregnant women with iron deficiency anemia (IDA) is due to an increase in morbidity and adverse effects on the course and outcome of the gestational process, the state of the fetus and newborn.The objective of this study was the comparative assessment of the frequency of complications of labor and the postpartum period in women who received intravenous and oral iron preparations during pregnancy.Material and methods. The study included 140 pregnant women. The mean age of the patients was 31.75 (19; 49) years. Results. Pregnant women with IDA, after a single administration of intravenous preparation of iron carboxymaltosate, had pronounced stable dynamics of hematological and ferrokinetic blood parameters, as well as the low frequency of postpartum complications, compared to the oral preparation of iron (III) hydroxide polymaltosate.